INCREASING READING MASTERY BY USING A SCANNING STRATEGY - gunaldi masbiran (Indonesian Journal of Integrated English Language Teaching, 2018)
The aim of this research was to find out whether the students’ reading comprehension could be improved through scanning strategy at the Second Semester Students of Academy of  Foreign Languages at Persada Bunda Foundation in Pekanbaru. The problem was students’ low in reading comprehension and lack of knowledge of reading technique. The research was classroom action research. The participants of this research were the Second Semester Students of Academy of  Foreign Language at Persada Bunda Foundation in Pekanbaru. They are consisted of 21 students. The other participant was one of the English lecturer as the researcher’s collaborator. This research was conducted in two cycles, each cycle consisted of three meetings. The data in this research were divided into two major types namely, quantitative and qualitative data. The quantitative data were gathered through reading comprehension test. The qualitative data were collected through observation, and field notes. The result of the analysis showed that the students grades improved after using the scanning technique. The improvement happened on each cycle at the research. The improvement of students’ reading comprehension scores were influenced by factors such as motivation, interest, and classroom atmosphere. Thus, it was conclude that scanning can improve students’ reading comprehension. The technique also increases students’ speed in reading comprehension that can be used by students of Academy of Foreign Language at Persada Bunda Foundation and others. Therefore, the scanning technique is suggested to be used by the students and lecturer in teaching and learning reading comprehension at the Academy of Foreign Language of Persada Bunda Foundation in Pekanbaru